Berectones A and B: Two new rotenoids from the aerial parts of Boerhavia erecta. Issue 20 (13th October 2022) - Dao, Thi-Bich-Ngoc; Duong, Thuc-Huy; Dao, Ngoc-Van-Trang; Vo, Huu-Canh; Pham, Nguyen-Kim-Tuyen; Nguyen, Huy Truong; Nguyen, Ngoc-Hong; Sichaem, Jirapast
Abstract: Two previously unreported rotenoids, berectones A and B (1 and 2 ), along with four known compounds, 3, 3′, 4′-tri- O -methylellagic acid (3 ), kaempferol (4 ), 7, 4′-dihydroxy-8-methoxyisoflavone (5 ), and trans-N -caffeoyltyramine (6 ) were isolated from the aerial parts of Boerhavia erecta . The structures of all isolated compounds were fully characterized using spectroscopic data, as well as comparison with the previous literature. Compound 6 exhibited the strongest inhibitory activity toward α- glucosidase with IC50 value of 4.74 µM.